La estrategia Obama: La construcción de una marca exitosa - Córdova Bojórquez, Gustavo (Frontera Norte, 2017)
Andrés Valdez, José Eduardo Borunda, Bertha Campos, Bertha Gutiérrez, Sergio Díaz y Joaquín Sánchez, Universidad Autónoma de Chihuahua/Academia de Ciencias Administrativas, A. C./Prometeo Editores, 2010